La aplicación de la literatura infantil y su incidencia en el desarrollo del lenguaje oral de los niños y niñas de primer grado de educación básica de la escuela Libertador Bolívar de la parroquia Chongón, cantón Guayaquil, provincia del Guayas. Período lectivo 2014 - 2015. lLneamientos alternativos - Pérez Zambrano, María Verónica (2015)
This research was part of an analytical, descriptive and explanatory study "IMPLEMENTATION OF CHILDREN'S LITERATURE AND ITS IMPACT ON THE DEVELOPMENT OF ORAL LANGUAGE OF CHILDREN FIRST DEGREE OF BASIC EDUCATION SCHOOL" LIBERTADOR BOLÍVAR "DE LA Chongón PARISH, CANTON GUAYAQUIL, PROVINCE OF GUAYAS. LECTIVO PERIOD 2014 - 2015 ". ALTERNATIVE GUIDELINES, the same that was developed according to the Regulation of Academic System of the National University of Loja. The overall objective raised was: Introduce to the educational community the importance of the implementation of the Children's Literature in Oral Language Development of Children First Grade Basic Education School "Liberator Bolívar" of Chongon parish, canton Guayaquil, Guayas Province. Lectivo 2014-2015. Scientific, Inductive-Deductive, Analytic-Synthetic, Descriptive and Statistical Model: methods were used. The techniques and instruments used were: The Survey aimed at teachers of children in First Grade Basic Education "Liberator Bolívar" School, to identify the types of children's literature that used in the daily work; and the Test Zimmerman aimed at children from first grade of Basic Education of the "Liberator Bolívar" School to assess Oral Language Development. Analyzed the results of the survey of teachers it is concluded that: 100% of the teachers state that in the daily work using the following types of children's literature: folk tales, fables, rhymes, riddles, tongue twisters and 50% use stories classics. . According to the results of the test Zimmerman concludes that: 67% of children surveyed girls are in the range of 30-40 which corresponds to a development of Language Oral Normal, 29% are located in the range of 50 Excellent 80 equivalent to 4% and in the range of 10 to 20 corresponding to Low.